PEMASANGAN EYELASH EXTENSION DALAM UNDANG-UNDANG PERLINDUNGAN KONSUMEN NOMOR 8 TAHUN 1999 DAN HUKUM ISLAM - Shakina Shakina; Sukardi Sukardi; Abu Bakar (Al-Aqad, 2023)
This research aims to examine the installation of Eyelash Extensions in Islamic law. This research has 2 problem formulations, namely: 1) Eyelash Extension installation practice. 2) Review of Consumer Protection Law No. 8 of 1999 and Islamic law. The type of research used is qualitative research. As far as its implementation, this research is alluded to as field research, which is to find events that are the object of continuous examination, to obtain the latest and direct data on Eyelash Extension Installation in Consumer Protection Law Number 8 of 1999 and Islamic Law. In practice, researchers observe, that business actors do not carry out all the rights that should be obtained by consumers following Article 7 of the Law. In terms of the installation of Eyelash Extension in Islamic Law is haram. The first is that the Eyelash Extension is included in changing Allah's creation without any reason that requires changing Allah's creation. The existence of the prohibition is divided into two, namely related to a sense of ingratitude for God's creation. Secondly, Eyelash Extension is included in tabarruj because of excessive self-adornment. This activity can also endanger oneself.